The Effect of Unsuitable Drinking Water Sources and Unsuitable Toilets on the Incidence of Stunting in the Sampanahan District of Kotabaru Regency - Bayu Saputra; Muhammad Nur Iman Ridwan; Jamaluddin Jamaluddin (Journal of World Science, 2025)
This study examines the influence of unsuitable drinking water sources and inadequate sanitation facilities on stunting incidence in Sampanahan District, Kotabaru Regency, using a mixed-methods explanatory sequential design. Quantitative data were collected from 201 mothers of children under five through questionnaires, while qualitative insights were obtained via interviews with five key informants. Statistical analysis using logistic regression showed no significant effect of unsuitable drinking water sources (p = 0.376) or inadequate latrines (p = 0.756) on stunting incidence. The Nagelkerke R Square value of 0.006 indicated that these factors contributed only 0.6% to stunting cases. However, qualitative findings revealed that community perceptions strongly linked both factors to stunting through indirect pathways such as recurrent infections and environmental contamination. Despite statistical insignificance, field observations confirmed limited access to proper water sources and sanitation facilities, particularly in geographically constrained areas like Rampa Manunggul Village. The study concludes that while unsuitable drinking water sources and latrines may not demonstrate direct statistical correlation with stunting in this context, they remain practically relevant for stunting prevention efforts. These findings suggest the need for integrated interventions that address both direct nutritional factors and underlying environmental determinants to effectively reduce stunting prevalence in similar resource-limited settings.